174 - CIRCUIT OF PLAY: THE CURRICULUM IN MOTION IN EARLY CHILDHOOD EDUCATION (Fiep Bulletin - online, 2011)
This socialization is part of the work of the Office of Early Childhood Education Hall Pratinha (UMEI) of the Municipal School Belém Pa, in the year 2008 that is based on theoretical studies of childhood Moss (2002) Junqueira Filho (2006 ) Gallardin (1996), Loris Mallaguzi, Carolyn Edwards (1999), Machado (2002), among others. The methodological approach includes the curriculum from multiple languages involving building projects host circuit of games, projects involving classes bimonthly coordinator / teachers / children and families. The objective is to provide a quality early childhood education, ensuring a consistent and meaningful learning, socialized through the channels of the games that represent the global movement of children with playful universe. The relevant matches from this organization methodology, we find the valuation of several childhood, the role of the child and the playfulness and appreciation of children's play, building an early childhood education humanizing quality and the social experience in a warm, stimulating and lively, and the involvement of educators in the organization of spaces in interactive entertainment and education.
Keywords: Multiple languages; Exploitation of Children; playfulness